Peningkatan Kualitas Pembelajaran PJOK melalui Integrasi Buku Cetak dan Website Interaktif di SD Tahfidz Al-Jamiel - Muhammad Noor Habil; Hilda Dwi Junianti; Ratna Eva Wati; Zaitun Qamariah; Setria Utama Rizal (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity was motivated by the need to create Physical Education, Sports, and Health (PJOK) learning that is more engaging, interactive, and suited to the characteristics of elementary school students in the digital era. The service team identified a significant potential to integrate print-based learning media with interactive websites as an innovative solution to address monotonous and less visual learning processes. This activity was carried out at SD Tahfidz Al-Jamiel, involving second-grade students as the primary subjects, while teachers acted as facilitators and observers of the learning process. The service method adopted the ABCD (Asset-Based Community Development) approach by utilizing local assets such as students' enthusiasm as digital natives, adequate school facilities, and the school's openness to educational innovation. The activity was implemented through several stages: initial observation, program planning, implementation of learning using interactive media, and a simple evaluation of the activity’s impact.The results of this activity indicated that integrating printed books and interactive websites could enhance students' interest and participation in PJOK learning. Students appeared more active, enthusiastic, and found it easier to understand locomotor movement material being taught. Teachers also responded positively to the media used. This activity demonstrates that digital-based learning transformation can be conducted in a simple and practical manner within the elementary school context and holds great potential for replication in other schools.